Reinventing the Lacandón : Subaltern Representations in the Rain Forest of Chiapas - Gollnick, Brian, 1968- (Book collections on Project MUSE., 2008)
"Before massive deforestation began in the 1960s, the Lacandon jungle, which lies on the border of Mexico and Guatemala, was part of the largest tropical rain forest north of the Amazon. The destruction of the Lacandon occurred with little attention from the international press - until January 1, 1994, when a group of armed Maya rebels led by a charismatic spokesperson who called himself Subcomandante Marcos emerged from jungle communities and briefly occupied several towns in the Mexican state of Chiapas. These rebels, known as the Zapatista National Liberation Army, became front-page news around the globe, and they used their notoriety to issue rhetorically powerful communiques that denounced political corruption, the Mexican government's treatment of indigenous peoples, and the negative impact of globalization. As Brian Gollnick reveals, the Zapatista communiques had deeper roots in the Mayan jungle than Westerners realized - and he points out that the very idea of the jungle is also deeply rooted, though in different ways, in the Western imagination."--BOOK JACKET.